FT/TFL1: Calibrating Plant Architecture - Moraes, Tatiana Souza; Dornelas, Marcelo Carnier; Martinelli, Adriana Pinheiro (Frontiers in Plant Science, 2019)
There is a very large diversity in plant architecture in nature. Over the past few years, novel theoretical concepts and analytical methods have emerged as powerful tools to understand important aspects of plant architecture. Plant architecture depends on the relative arrangement of three types of organs: leaves, shoots, and ﬂowers. During plant development, the architecture is modulated by the balance of two homologous proteins: FLOWERING LOCUS T (FT) and TERMINAL FLOWER 1 (TFL1). The FT/TFL1 balance defines the plant growth habit as indeterminate or determinate by modulating the pattern of formation of vegetative and reproductive structures in the apical and axillary meristems. Here, we present a summarized review of plant architecture and primarily focus on the FT/TFL1 balance and its effect on plant form and development. We also propose passion fruit as a suitable model plant to study the effect of FT/TFL1 genes on plant architecture.